Cuentos gráficos fantásticos de inspiración onírica - Lascano Granda, Eunice Nashely (2014)
This thesis makes a study of fantasy and dreamlike as a source of creativity in literature, film and illustration checking fertilization of ideas. Likewise own personal dream elements analysis is made, showing sketches, diary entries dreams and an exploration of personal background. Subsequently, two stories illustrated with an originality that comes from the dreamlike inspiration is created. This work is support in the creation or research that is related to Fantasy, Illustration and Dreaminess, because it shows how dreams can be important in the life of a person, in this case an artist, to the point of needing to be externalized, enriching creativity in illustration and storytelling.